(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
The aim of this work was to describe a case of catastrophic fracture of the distal lateral condyle of the III metatarsal bone, with propagation to the diaphysis in a Thoroughbred racehorse. A complete necropsy was performed on a 5-year-old male Thoroughbred racehorse, which had to be euthanized as a result of a serious metatarsus injury that occurred in a 1000-meter race. The examination of the musculoskeletal system focused on the cannon and fetlock region of the fractured limb. Serial sagittal sections of the epiphyses were performed to examine, macroscopically and by radiological study, the bone surfaces in depth. The condylar fracture of the III metatarsal bone involved the lateral condyle and originated the diaphyseal fracture. The areas of sclerosis observed in the subchondral and epiphyseal bone were indicative of intense bone remodeling over time and represented the starting point of the metatarsal fracture. Some factors are mentioned, which may have increased the risk of fatality in this case. The postmortem study allowed the recognition and characterization of both the catastrophic fracture and the pre-existing injuries.